2011
DOI: 10.5194/angeo-29-1739-2011
|View full text |Cite
|
Sign up to set email alerts
|

Whistler-Langmuir oscillitons and their relation to auroral hiss

Abstract: Abstract.A new type of oscilliton (soliton with superimposed spatial oscillations) is described which arises in plasmas if the electron cyclotron frequency e is larger than the electron plasma frequency ω e , which is a typical situation for auroral regions in planetary magnetospheres. Both highfrequency modes of concern, the Langmuir and the whistler wave, are completely decoupled if they propagate parallel to the magnetic field. However, for oblique propagation two mixed modes are created with longitudinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…This model starts from the fluid equations of a cold main plasma and a drifting warm minor electron population described by a water‐bag distribution. Details of the dispersion analysis are described in Sauer and Sydora (2010, 2011). Aside from the absence of strong damping of the beam modes in the fluid model, there is a reasonable agreement between both approaches.…”
Section: Lower‐band Highly Oblique Whistler Waves Driven By Landau‐rmentioning
confidence: 72%
“…This model starts from the fluid equations of a cold main plasma and a drifting warm minor electron population described by a water‐bag distribution. Details of the dispersion analysis are described in Sauer and Sydora (2010, 2011). Aside from the absence of strong damping of the beam modes in the fluid model, there is a reasonable agreement between both approaches.…”
Section: Lower‐band Highly Oblique Whistler Waves Driven By Landau‐rmentioning
confidence: 72%
“…An important point is the evolution of the wave number spectrum of the electric field during and after saturation of the beam instability. Previous particle simulations (Sauer & Sydora, 2011, 2012 have shown that a wave number shift of the primary unstable Langmuir wave from k~ω e /V b to smaller values takes place, obviously caused by plateau formation and related effects. The detailed mechanism behind this conversion remained unclear, but the crucial role of ion dynamics was obvious.…”
Section: Long-term Evolution Of Beam-plasma Interaction and Its Intermentioning
confidence: 96%
“…Our present investigations of electromagnetic wave generation near to the electron plasma frequency ω e go back to particle‐in‐cell (PIC) simulations and their interpretation in the previous work by Sauer and Sydora (, ). There, beam‐plasma interaction in a magnetized plasma has been studied under different plasma conditions, in particular, by varying the ratio G = Ω e / ω e between the electron cyclotron frequency Ω e and the electron plasma frequency ω e .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations